2018
DOI: 10.1007/s11920-018-0925-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and Mental Health: Recent Advances

Abstract: While evening chronotype is most consistently associated with severity of mood disorder symptoms, emerging evidence implicates evening chronotype as a transdiagnostic correlate of substance use severity, anxiety symptoms, attentional difficulties, and maladaptive behaviors such as aggression. Longitudinal studies point to the possibility that evening chronotype precedes problematic substance use, depression, and anxiety. Neural processes related to reward and affective regulation may underlie associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 133 publications
13
130
2
6
Order By: Relevance
“…However, it is interesting to notice the significant correlation between the chronotype‐PRS and the MDD‐PRS and BD‐PRS, suggesting that patients with higher scores for a morning type chronotype present lower risk scores for both mood disorders. These results are in line with previous evidence showing that the chronotype most commonly associated with MDD and BD is the evening type 61 …”
Section: Discussionsupporting
confidence: 93%
“…However, it is interesting to notice the significant correlation between the chronotype‐PRS and the MDD‐PRS and BD‐PRS, suggesting that patients with higher scores for a morning type chronotype present lower risk scores for both mood disorders. These results are in line with previous evidence showing that the chronotype most commonly associated with MDD and BD is the evening type 61 …”
Section: Discussionsupporting
confidence: 93%
“…29 Secondly, the mediating factor for the development of periodontal disease may be that E-types have more problematic eating habits such as skipping breakfast, coffee consumption and night eating and are more prone to smoking and alcohol and substance use. 17,[30][31][32] Finally, recent studies indicated that periodontal disease may be associated with psychological factors such as stress, depression and anxiety and these findings may be an indicator that periodontal disease will develop more easily in E-types individuals who experience these psychological symptoms more than M-types. [33][34][35] Although no correlation was found between chronotype preferences and the DMFT index, and number of endodontically treated teeth in our study, a statistically significant relationship was found with the MEQ scores and severity of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we lacked information on chronotype. The evening chronotype, which is normally more frequent among night than day workers, has been independently associated with the risk and severity of depression (57). This might have biased the results towards the null if workers with evening chronotype, rather than other chronotypes, tended to change working schedules to non-night work due to depressive symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 99%